Technology and the Task of Planetary Thought: Review of Huk, Y. (2024). Machine and Sovereignty: For a Planetary Thinking. Minnesota: University of Minnesota Press. (341 pages) - de Boer, Bas (Journal of Human-Technology Relations, 2025)
N/A